Expedient synthesis of 1,6-anhydro-α-D-galactofuranose, a useful intermediate for glycobiological tools - Baldoni, Luciana (2014)
A new and efficient three-step procedure for the synthesis of 1,6-anhydro-α-D-galactofuranose is described. The key step involves the formation of the galactofuranosyl iodide by treatment of per-O-TBS-D-Galf with TMSI, the selective 6-O-desilylation by an excess of TMSI, and the simultaneous nucleophilic attack of the 6-hydroxy group on the anomeric carbon, with the iodide as a good leaving group. This compound is a good precursor for building blocks for the construction of 1→6 linkages.